NEOLIBERAL FUEL SUBSIDY REFORMS: IMPACT ON COMMERCIAL DRIVERS' LIVELIHOODS IN AGWADA, NIGERIA - Audu Yusufu, Ahmed; Audu, Bello; Audu, Abu (African Journal of Social and Behavioural Sciences, 2024)
This study provides a nuanced analysis of the micro-level socio-economic consequences of fuel subsidy removal in rural Nigeria, focusing on commercial drivers in Agwada, Nasarawa State. Grounded in Welfare Economics Theory (WET), the research offers a comprehensive framework for understanding the welfare and distributional effects of such economic policies. Employing a mixed-methods approach, the study combines primary data, obtained through structured questionnaires administered to commercial drivers at Mararaba Agwada motor park, with secondary data from peer-reviewed scholarly sources and reputable digital databases. Quantitative analysis of the survey data reveals that fuel subsidy removal has significantly increased fuel prices, resulting in an over 50% rise in operational costs and a corresponding decline in drivers’ earnings. These economic pressures have led to reduced disposable income, increased indebtedness, depleted savings, and restricted access to healthcare for drivers and their families. At the community level, the cascading effects include suppressed market activities, declining school enrolment, and reduced employment opportunities in vehicle maintenance. Despite adopting coping mechanisms such as fare increases, route optimization, income diversification, and extended work hours, drivers continue to face substantial economic hardships. The study underscores the need for targeted interventions, including low-interest loans, infrastructure development, affordable healthcare insurance, and reinstated fuel subsidies. These policy recommendations aim to alleviate the economic burden on commercial drivers and promote socio-economic stability and resilience within their communities.